Learning to teach English in the secondary school [ a companion to school experience - Davison, Jon , 1949-; Dowson, Jane , 1955- (Learning to teach subjects in the secondary school series, 2009)
ocused on the key skills needed to teach English at the secondary school level, this text covers a range of issues that include - use of new technology, reading, writing, speaking, listening, drama and the teaching of grammar